THE INDONESIAN-ARABIC CODE MIXING ON FACEBOOK AMONG THE MEMBER OF WANITA INDONESIA BERCADAR (WIB) COMMUNITY - Dwi Warry Octaviana (STKIP PGRI Tulungagung, 2019)
Facebook has become one of the main communication media which people utilize to keep in contact with friends and acquaintances. Thus, this makes it an appealing medium of spoken-written language to identify trends of code mixing among them in informal social domains. This site popularity has aroused the researcher’s interest to choose it as a ground for this study. The aim of the study was to identify the form of code mixing which was frequently used by the member of Wanita Indonesia Bercadar (WIB) community. This research applied descriptive qualitative method. The data analysis of this research would be based on the observation of Facebook status and wall interaction. The data were analyzed using the observation checklist. Then, the data were analyzed based on the linguistic form of code mixing by Suwito’s theory. The results showed that word insertion was the most frequent inserted level of code mixing on Facebook among the member of Wanita Indonesia Bercadar (WIB) community.